Effect mechanism of ultrasound pretreatment on fibrillation Kinetics, physicochemical properties and structure characteristics of soy protein isolate nanofibrils - Hu, Anna; Li, Liang (Ultrasonics sonochemistry, 2021)
•Ultrasound can increase the formation rate of soy protein isolate nanofibrils.•Ultrasound-pretreated soy protein isolate nanofibrils has a smaller particle size.•Ultrasound can increase β-sheet contents of SPI nanofibrils, promoting the nanofibrils formation.•Ultrasound can promote protein unfolding and exposing more binding sites. Self-assembly of soy proteins into nanofibrils is gradually considered as an effective method to improve their technical and functional properties. Ultrasound is a non-thermal, non-toxic and environmentally friendly technology that can modulate the formation of protein nanofibrils through controlled structural modification. In this research, the effect of ultrasound pretreatment on soy protein isolate nanofibrils (SPIN) was evaluated by fibrillation kinetics, physicochemical properties and structure characteristics. The results showed that the optimum ultrasound condition (20% amplitude, 15 min, 5 s on-time and 5 s off-time) could increase the formation rate of SPIN by 38.66%. Ultrasound reduced the average particle size of SPIN from 191.90 ± 5.40 nm to 151.83 ± 3.27 nm. Ultrasound could increase the surface hydrophobicity to 1547.67 in the initial stage of nanofibrils formation, and extend the duration of surface hydrophobicity increased, indicating ultrasound could expose more binding sites, creating more beneficial conditions for nanofibrils formation. Ultrasound could change the secondary and tertiary structure of SPIN. The reduction of α-helix content of ultrasound-pretreated soy protein isolate nanofibrils (USPIN) was 12.1% (versus 5.3% for SPIN) and the increase of β-sheet content was 5.9% (versus 3.5% for SPIN) during fibrillation. Ultrasound could accelerate the formation of SPIN by promoting the unfolding of SPI, exposure of hydrophobic groups and formation of β-sheets. Microscopic images revealed that USPIN generated a curlier and looser shape. And ultrasound reduced the zeta potential, free sulfhydryl groups content and viscosity of SPIN. SDS-PAGE results showed that ultrasound could promote the conversion of SPI into low molecular weight peptides, providing building blocks for the nanofibrils formation. The results indicated that ultrasound pretreatment could be a promising technology to accelerate SPIN formation and promote its application in food industry, but further research is needed for the improvement of the functional properties of SPIN.